2017
DOI: 10.1148/radiol.2016160685
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of MR Elastography and Vibration-controlled Transient Elastography in the Detection of Hepatic Fibrosis in Patients with Severe to Morbid Obesity

Abstract: Purpose To evaluate the diagnostic performance and examination success rate of MR Elastography (MRE) and Vibration-Controlled Transient Elastography (VCTE) for detecting hepatic fibrosis in patients with severe to morbid obesity. Methods This prospective and HIPAA (The Health Insurance Portability and Accountability Act) compliant study was IRB approved. A total of 111 patients (71 women) participated with written informed consent. Patients underwent MRE with 2 readers and VCTE with 3 observers to acquire li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 48 publications
(54 reference statements)
5
128
2
1
Order By: Relevance
“…To increase the sample size and improve the study power, we added a retrospective cohort of 87 NAFLD patients with liver biopsy and mf3D‐MRE at 40Hz and 60 Hz, as described . The median time interval between liver biopsies and MRE was 27 (IQR = 20‐30) days.…”
Section: Resultsmentioning
confidence: 99%
“…To increase the sample size and improve the study power, we added a retrospective cohort of 87 NAFLD patients with liver biopsy and mf3D‐MRE at 40Hz and 60 Hz, as described . The median time interval between liver biopsies and MRE was 27 (IQR = 20‐30) days.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, obscure terms used in the studies, eg, poor wave propagation, which can be caused by iron overload, respiratory artifact, and obesity, also limited to explore other potential factors. For example, there are mixed results on whether obesity or high BMI would affect the technical failure of MRE . Since high BMI is the major cause of failure in US elastography, MRE can be an alternative for obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition liver biopsy results are variable due to sampling errors related to both small sample size and spatial variation in degree of fibrosis and variability of pathologist interpretation [9,10]. A recent study reported a difference of at least one fibrosis stage in 30% of series of 111 biopsy specimens evaluated by different pathologists [11]. While liver biopsies remain an important clinical tool, modern medical management of liver disease often relies on regular, interval assessments of liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%